Synthesis, Antimalarial Activity and Molecular Dynamics Studies of Pipecolisporin: A Novel Cyclic Hexapeptide with Potent Therapeutic Potential - Nety Kurniaty; Taufik Muhammad Fakih; Rani Maharani; Unang Supratman; Ace Tatang Hidayat; Nurhidanatasha Abu Bakar; Xiaoshuang Wei (Molecules)
Malaria, caused by Plasmodium species and transmitted by Anopheles mosquitoes, continues to pose a significant global health threat. Pipecolisporin, a cyclic hexapeptide isolated from Nigrospora oryzae, has emerged as a promising antimalarial candidate due to its potent biological activity and stability. This study explores the synthesis, antimalarial activity, and computational studies of pipecolisporin, aiming to better understand its therapeutic potential. The peptide was successfully synthesized using Fmoc-based solid-phase peptide synthesis (SPPS) followed by cyclization in solution. The purified compound was characterized using HPLC and mass spectrometry, confirming a molecular ion peak at m/z [M + H]+ 692.4131, which matched the calculated mass. Structural verification through 1H- and 13C-NMR demonstrated strong alignment with the natural product. Pipecolisporin exhibited significant antimalarial activity with an IC50 of 26.0 ± 8.49 nM, highlighting its efficacy. In addition to the experimental synthesis, computational studies were conducted to analyze the interaction of pipecolisporin with key malaria-related enzymes, such as dihydrofolate reductase, plasmepsin V, and lactate dehydrogenase. These combined experimental and computational insights into pipecolisporin emphasize the importance of hydrophobic interactions, particularly in membrane penetration and receptor binding, for its antimalarial efficacy. Pipecolisporin represents a promising lead for future antimalarial drug development, with its efficacy, stability, and binding characteristics laying a solid foundation for ongoing research.